Going beyond the EFL teachers’ beliefs on authentic assessment: Reframing the five-dimensional approach - Rozanah Katrina Herda; Ima Widyastuti; Maria Corazon Saturnina A Castro; Angga Damayanto (Universitas Sarjanawiyata Tamansiswa, 2022)
The 21st-century EFL teachers should focus more on students’ real performance, and authentic assessments become the most suitable assessment type that demonstrates students’ knowledge to perform real-world tasks in their real and meaningful context. The objectives of this qualitative study were to reveal the teachers’ beliefs in authentic assessment and propose an authentic assessment model adapted to Gulikers et al.'s five-dimensional framework. This study involved 37 EFL teachers in Indonesia from three education levels. The data were collected through a close-ended questionnaire made online and then analyzed using descriptive statistics. The findings of this study showed that teachers believed in the urgency of authentic assessment and the need to have a guideline that could be used to design appropriate authentic assessments. Additionally, by linking up to the need to design an ideal authentic assessment, the writers proposed a framework that not only focuses on the result but also considers the important elements in designing an authentic assessment that not many teachers know. Hopefully, the proposed framework will benefit educators, practitioners, and researchers who need new insight into the procedure to conduct an authentic assessment for their students.